2014
DOI: 10.1051/matecconf/20141405003
|View full text |Cite
|
Sign up to set email alerts
|

Origins of misorientation defects in single crystal castings: A time resolved in situ synchrotron X-ray radiography study

Abstract: Abstract. The presence of grain boundaries in single crystal castings is intolerable owing to the detrimental impact on creep and fatigue behaviour. Whilst the origins of many defects such as freckles have been understood since the 1970s, other defects such as slivers, or indeed the small mosaicity observed in many castings have eluded comprehensive treatments. In the present work, in situ X-ray imaging has been used to examine the origin of misorientation defects that arise during solidification. Dendrite def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…Other strains can be induced in the base metal due to the microscale plasticity which is caused by differential thermal contraction of metal, mould, and core [47][48][49] . It was estimated that when the mould and core do not crush or deform suf ciently or crack the metallic components can impose a strain value of about 2 3% 46) , which is over the critical plastic strain (0.2%) for the recrystallization of turbine blades 47) . These processes can lead to extensive plastic deformation being imparted to an as-cast turbine blade at high temperature and this can be responsible for strain relaxation through recrystallization during subsequent heat treatments.…”
Section: Surface Defects Formed During Subsequent Heatmentioning
confidence: 99%
“…Other strains can be induced in the base metal due to the microscale plasticity which is caused by differential thermal contraction of metal, mould, and core [47][48][49] . It was estimated that when the mould and core do not crush or deform suf ciently or crack the metallic components can impose a strain value of about 2 3% 46) , which is over the critical plastic strain (0.2%) for the recrystallization of turbine blades 47) . These processes can lead to extensive plastic deformation being imparted to an as-cast turbine blade at high temperature and this can be responsible for strain relaxation through recrystallization during subsequent heat treatments.…”
Section: Surface Defects Formed During Subsequent Heatmentioning
confidence: 99%
“…Since then, various studies on mosaicity have been conducted considering different types of samples, including cylindrical laboratory specimens [11,32,33], complex superalloy turbine blades [38][39][40][41] and other geometries [42][43][44][45][46]. It has been suggested that SX mosaicity is caused by the deformation of dendrites in the mushy zone during solidification [38,42,43,[46][47][48][49]. In a directional solidification process SXs form by the growth of dendritic arrays.…”
Section: Introductionmentioning
confidence: 99%
“…In several publications, thermal and shrinkage stresses were invoked to explain the deformation of dendrites [38,[50][51][52][53]. Other explanations, such as convective forces [54][55][56], precipitation-related phenomena [45], interactions with the mold wall [47][48][49], gravity [49] and asymmetric distributions of the solute around dendrite stems [46] have also been put forward. [15,[28][29][30]) affect performance and how they can be controlled, there is one aspect which has received insufficient attention.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations